Guanine-based spin valve with spin rectification effect for an artificial memory element - Nicusor Iacob; Cristina Chirila; Mama Sangaré; Andrei Kuncser; Anda E. Stanciu; Marcela Socol; Catalin C. Negrila; Mihaela Botea; Claudiu Locovei; Gabriel Schinteie; Aurelian C. Galca; Anca Stanculescu; et al. (Heliyon)
Non-volatile electronic memory elements are very attractive for applications, not only for information storage but also in logic circuits, sensing devices and neuromorphic computing. Here, a ferroelectric film of guanine nucleobase is used in a resistive memory junction sandwiched between two different ferromagnetic films of Co and CoCr alloys. The magnetic films have an in-plane easy axis of magnetization and different coercive fields whereas the guanine film ensures a very long spin transport length, at 100 K. The non-volatile resistance states of the multiferroic spintronic junction with two-terminals are manipulated by a combined action of small external magnetic and electric fields. Thus, the magnetic field controls the relative orientation of the magnetization of the metallic ferromagnetic electrodes, that leads to different magnetoresistance states. The orientation and the magnitude of the electric field controls the orientation of the polarization of the guanine ferroelectric barrier, that leads to different electroresistance states, respectively. Moreover, we have observed a strong interfacial coupling of the two parameters. Consequently, positive and negative magnetoresistance hysteresis loops corresponding to spin rectification effects and non-hysteretic (erased) resistive states are manipulated with the electric field by switching the orientation of the electrical polarization of the organic ferroelectric.